ANALISIS YURIDIS MENGENAI BENTUK PERLINDUNGAN RAHASIA BANK DAN SANKSI TERHADAP PELANGGARAN RAHASIA BANK - Tumpak Hasiholan Manurung; Maryati Bachtiar; Dasrol ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Banking is everything that concerns about banks, including institutional,business activities, as well as the manner and process of operation. To avoidmisuse of customer financial hence made a special rule that prohibits banks toprovide recorded information to anyone associated with the customer's financialsituation, savings and storage as set out in Pasal 1 angka 28 Undang-UndangNomor 10 Tahun 1998 tentang Perubahan Atas Undang-Undang Nomor 7 Tahun1992 tentang Perbankan, which states that bank secrecy is everything related tothe storage of information about your customers and their savings. The purpose ofthis thesis is to investigate the problems Banking Act already provides legalcertainty regarding the form of protection that is done by the banks to protectconfidential client or not, as well as the Banking Act already provides legalcertainty in terms of sanctions for the banks were negligent in maintainingbanking secrecy or not.This type of research can be classified into types of normative legalresearch, since the study was conducted by collecting data in the literature(library research) accompanied by collecting data and read through regulatoryreferences, magazines, the internet and other sources, and then selected the data -the data is worth to support writing.From the research problem there are 2 main things that can be inferred.First, the Banking Act not provide legal certainty regarding the form of banksecrecy protection carried out by the bank in secrecy customers. Second, theBanking Act not provide legal certainty in terms of sanctions for the banks werenegligent in maintaining banking secrecy. Suggestions Author, First, the need forthe addition of a form of protection provided by the banks to customers about theconfidentiality of Undang-Undang Nomor 10 Tahun 1998 tentang PerubahanAtas Undang-Undang Nomor 7 Tahun 1992 tentang Perbankan, in order to createlegal certainty and confidence to guarantee customers in saving money in anybank. Secondly, a need for the addition in the field of civil and criminal penaltiesto protect customers who are weak in Undang-Undang Nomor 10 Tahun 1998tentang Perubahan Atas Undang-Undang Nomor 7 Tahun 1992 tentangPerbankan, in order to create legal certainty and confidence guarantee forcustomers in saving funds at any bank.Keywords: Protection-Sanctions-Secret Bank